Aplikasi Sistem Keamanan Brankas Menggunakan E-KTP Berbasis Android - Tria Aprilianto; Samsul Arifin; Sunu Jatmika (Jurnal Teknika, 2022)
Combination locks are also easy to break into by thieves. Currently, the use of RFID (Radio Frequency Identification) technology in Indonesia is starting to develop, one of which is an e-Ktp card that already has an RFID chip on it, but its utilization is still lacking. remote safe using Internet Of Things technology which is monitored through a smartphone application. The way this tool works is that the safe is connected to the internet through a tool called Nodemcu Esp8266 to send ID data on the E-KTP, door sensor data and vibration sensor data to the database. Where the author uses the Firebase Realtime Database as an online database, after the ID data is stored in the database, it is then sent to an Android-based smartphone application which is also a second security and can monitor and control the safe door.